2018
DOI: 10.1063/1.5019989
|View full text |Cite
|
Sign up to set email alerts
|

Homogeneous dielectric barrier discharges in atmospheric air and its influencing factor

Abstract: The stable homogeneous dielectric barrier discharge (DBD) is obtained in atmospheric 2–3 mm air gap. It is generated using center frequency 1 kHz high voltage power supply between two plane parallel electrodes with specific alumina ceramic plates as the dielectric barriers. The discharge characteristics are studied by a measurement of its electrical discharge parameters and observation of its light emission phenomena. The results show that a large single current pulse of about 200 μs duration appearing in each… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 9 publications
0
20
0
Order By: Relevance
“…The "shallow trap" effect on the surface of alumina ceramics provides additional seed electrons and forms a uniform discharge in the air. Ran et al [21,101] studied the influence of dielectric surface morphology on discharge mode using different dielectric materials with similar equivalent capacitance and barrier media with surface morphology as shown in Figure 16. The results showed that the surface morphology of the dielectric materials played an important role in the discharge mode.…”
Section: Air H-dbdmentioning
confidence: 99%
See 2 more Smart Citations
“…The "shallow trap" effect on the surface of alumina ceramics provides additional seed electrons and forms a uniform discharge in the air. Ran et al [21,101] studied the influence of dielectric surface morphology on discharge mode using different dielectric materials with similar equivalent capacitance and barrier media with surface morphology as shown in Figure 16. The results showed that the surface morphology of the dielectric materials played an important role in the discharge mode.…”
Section: Air H-dbdmentioning
confidence: 99%
“…Non-equilibrium atmospheric pressure plasma (N-APP) is a promising technology for generating high concentration reactive species at a relatively low gas temperature or room temperature [1-8], making it highly attractive for a variety of applications such as surface modification, decontamination of temperature-sensitive materials, and more [9][10][11][12][13][14][15]. Among the different methods used for generating N-APP, dielectric barrier discharge (DBD) is one of the most widely studied techniques and has been explored for more than a century [16][17][18][19][20][21][22]. In DBD, one or two dielectrics are inserted into the discharge circuit, which requires ignition of the discharge using alternating-current (AC) voltage or pulsed direct-current (DC) voltage.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In terms of IGBT device package insulation, Mark Sweet found that both N 2 pressure and gas type have a significant impact on the insulation strength through electric field simulation [22]. All in all, research into the influence of gas pressure on partial discharge mainly focuses on DC, AC voltage [5,6] and nanosecond pulse sequence [17,18,23]. The influence of N 2 pressure on the surface discharge under positive repetitive square voltage has rarely been investigated.…”
Section: Introductionmentioning
confidence: 99%
“…Besides, it was found by spectrum analysis that the proportion of the corresponding high-frequency components of the discharge current increases with the increase in gas pressure [6]. Research has indicated that the characteristics of dielectric barrier discharge (DBD) under nanosecond pulse sequence are affected by gas pressure [17,18].…”
Section: Introductionmentioning
confidence: 99%